Obszary współpracy transgranicznej gminy na przykładzie Marciszowa - Zawierucha, Stefan (The Areas of Transborder Cooperation in the Marciszów Commune, 2006)
The author of this article presents the possibilities of trans border cooperation in the Marciszów commune. He submits this cooperation in several areas. As far as the criterion of subjectivity is concerned, there are two areas: - the cooperation between local authorities and foreign local government's units, the economic, educational, sporting and environmental entities; - the cooperation between local organizations, such as: associations, clubs, etc.; Due to the usage of the objective classification it is possible to distinguish the areas of economic, cultural, educational, public security cooperation and the area environmental cooperation. Taking into consideration the last mentioned area, we can distinguish among in the following areas: a. Technical infrastructure. b. Environmental activities. c. The area of promotion. d. The area of labour market. e. The organising of economics fairs. f. The area of economic database. g. Tourism. h. Education. i. The area of culture and art. j. Sports and recreation. As it results from the above case study, one can observe the wide possibilities of the trans-border cooperation and the local authorities of the Marciszów commune implement them successively.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 463-471